Dakwah Multikultural (Dakwah Gus Miftah di Diskotik Hingga Gereja) - Zida Zakiyatul Husna (IAIN Padangsidimpuan, 2021)
It is known that Indonesia is a country that has various tribes, cultures, languages, religions, traditions and so on. This is what makes Indonesian society called a multicultural society. In the context of da'wah, this multicultural da'wah is more about how a da'i conveys his da'wah messages to mad'u who have different backgrounds. This study tries to discuss the methods used by Gus Miftah in conveying his da'wah among nightlife workers to non-Islamic communities. By using a descriptive qualitative paradigm, this study found that by means of an appearance that adapts to the place where the da'wah activities take place, the da'wah material starting from the basics discusses everyday life using language that is easy to understand, and the most important thing is not to judge the madam'. This is the key to the success of Gus Miftah's da'wah among night workers. And when he preached in front of non-Muslims, he prioritized the value of tolerance between religious communities.